Ljudski sposojenki âkovnik in môžer - Ludvik, Dušan (Traditiones (Ljubljana), 1999)
Loanwords are not only the theme of philosophical and linguistic research, but also a culturological and historical phenomenon. Their form can be identical to the one in the language they had been discusses two folk loanwords from Dolenjsko, âkovnik (a small cannon) and môžer (mortar)
Keywords: jezikoslovje; linguistics; Slovene; slovenščina; izposojenke; etimologija; etymology